2016
DOI: 10.1289/ehp.1509728
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular Markers within the Core Axis of Aging and Particulate Air Pollution Exposure in the Elderly: A Cross-Sectional Study

Abstract: Background:Telomere length and mitochondrial DNA (mtDNA) content are markers of aging and aging-related diseases. There is inconclusive evidence concerning the mechanistic effects of airborne particulate matter (PM) exposure on biomolecular markers of aging.Objective:The present study examines the association between short- and long-term PM exposure with telomere length and mtDNA content in the elderly and investigates to what extent this association is mediated by expression of genes playing a role in the tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 59 publications
5
80
1
Order By: Relevance
“…More recently, in an occupational study of truck drivers and office workers in Beijing, China, short term (averaged of 2–8 days) personal exposure to elemental carbon (EC) and PM 10 was associated with lower mtDNA content in all participants (Hou et al 2013). In a panel of elderly people living in Belgium, increased annual PM 2.5 was associated with decreased mtDNA content in blood (Pieters et al 2015). Only one other study has reported on the association between prenatal PM exposure and mitochondrial DNA content in cord blood (Janssen et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in an occupational study of truck drivers and office workers in Beijing, China, short term (averaged of 2–8 days) personal exposure to elemental carbon (EC) and PM 10 was associated with lower mtDNA content in all participants (Hou et al 2013). In a panel of elderly people living in Belgium, increased annual PM 2.5 was associated with decreased mtDNA content in blood (Pieters et al 2015). Only one other study has reported on the association between prenatal PM exposure and mitochondrial DNA content in cord blood (Janssen et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, the literature examining the relationship between particles and TL has been conflicting. Significant associations between annual PM 2.5 exposures and decreased TL have been reported [45], but in the NAS the relationship between annual BC exposures and decreased TL was only observed in never smokers [11]. The literature concerning short-term particle exposures is even more obscure.…”
Section: Discussionmentioning
confidence: 99%
“…We selected the 1-year average because it correlates well with averages of PM 2.5 , BC, and temperature over longer time windows and was available for a higher number of participants (Supplementary Table S1). Moreover, existing studies examining relationships between particle exposures and other biological markers of aging, like TL, report more consistent and biologically significant results when a 1-year particle exposure is utilized [6, 11, 4548]. …”
Section: Methodsmentioning
confidence: 96%
“…In addition to chronologic aging, TL is influenced by genetic factors (3) and varies considerably between individuals, even those with the same chronologic age. TL is also affected by numerous environmental factors (4); nutrients, foods, and dietary patterns (5); cigarette smoking (6); air pollution (7); physical activity (6,8); and chronic inflammation (9).…”
Section: Introductionmentioning
confidence: 99%